Combination of Anlotinib and Celecoxib for the Treatment of Abdominal Desmoid Tumor: A Case Report and Literature Review - Wang, Jianzheng; Li, Hongle; Wang, Hui; Li, Qingli; Bai, Xuanye; Lv, Huifang; Nie, Caiyun; Chen, Beibei; Xu, Weifeng; Tu, Shuiping; Chen, Xiaobing (Frontiers in Oncology, 2022)
Desmoid tumor is a rare disease, which is histologically characterized by local invasion, monoclonality, and fibroblast proliferation; and clinically characterized by a variable and often unpredictable course. The treatment of desmoid tumor is mainly surgical resection, but the recurrence rate is high. In recent years, a variety of treatment methods, including endocrine therapy, surgery, radiotherapy, chemotherapy, non-steroidal anti-inflammatory drugs, targeted drugs, interferon and more, have been used and achieved certain curative effects. In addition, in view of the inertia characteristics of desmoid tumor, observation is also a first-line scheme recommended by multiple guidelines. In the past, the research progress of targeted therapy for desmoid tumor is relatively slow and the curative effect is limited. Thus, targeted therapy is usually used as a remedial treatment after the failure of other conventional treatment methods. However, in recent years, with the rapid progress in the basic research of targeted therapy, some new targeted drugs are increasingly used for the clinical treatment of desmoid tumor and have achieved good results. Herein, we described a patient with aggressive fibromatosis in the abdominal cavity. Following a combined treatment using anlotinib and celecoxib, the patient achieved a partial response with mild toxicity. Simultaneously, the patient’s pain symptoms completely disappeared. This case indicates that the combination of anlotinib and NSAIDs could be a effective treatment for desmoid tumor.